Fluoride Release from Two Commercially Available Dental Fluoride Gels—In Vitro Study - Paweł J. Piszko; Aleksandra Piszko; Sylwia Kiryk; Jan Kiryk; Julia Kensy; Mateusz Michalak; Jacek Matys; Maciej Dobrzyński (Gels)
Fluoride has remained the most important ingredient in the prevention of tooth decay for many years. Therefore, fluoride prophylaxis should be highly individualized to provide patients with maximum benefits while minimizing the risk of toxic effects. This study aims to compare the degree of fluoride ion release from two commercially available dental fluoride gels (Fluormex and Fluor Protector Gel) in five different physiological solutions as well as their effect on pH. The concentration of fluoride ions and pH of tap water, distilled water, demineralized water, NaCl, and artificial saliva were evaluated before and after 48 h after dissolving and incubating the same amounts of gels. The concentration of fluoride ions was higher in solutions containing Fluormex than Fluor Pro-tector Gel (p < 0.05), with the highest concentration in demineralized water (16,917 ppm). It was accompanied by a decrease in pH below the critical value of 5.5 in all solutions except tap water. Not only the composition of the gel but also the chemical composition of the environment affects the release of fluoride ions. No relationship was found between the change in pH and the concentration of fluoride ions.